PENGARUH KOMPETENSI, INDEPENDENSI, AKUNTABILITAS DAN MOTIVASI AUDITOR TERHADAP KUALITAS AUDIT (Studi Empiris Pada Kantor Akuntan Publik Se Sumatera) - Sayandra, Recky Riandika; -, Kamaliah; -, Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine the influence of competence, independence, accountability and motivation on audit quality factors Public Accounting Firm se Sumatra. As the dependent variable is the quality of the audit, while the independent variables are competence, independence, accountability and motivation. The analysis method used in this research is descriptive statistical analysis method and multiple regression analysis. Research methods using census method, in which the entire population of 75 auditors spread on Public Accounting Firm in Sumatera used as a sample as well as research respondents. Prior to testing hypotheses, test the validity and reliability of the primary data questionnaire. Regression equations were then tested by the analysis of the classical assumption of Normality Test, Heteroskidastity test and Multicolinearity test. To see the effect of independent variables on the dependent variable is done through the analysis of t-test, F-test, a test of determination R (correlation coefficient), R Square (R2) and Adjusted R2. The results showed a partial and simultaneous factors of competence, independence, accountability and motivation have an impact on audit qualityKeywords: competence, independence, accountability and motivation, quality audit.